LEARNING MOTIVATION OF SLOW LEARNER IN ELEMENTARY SCHOOL - Pratia Amdany; Sularmi Sularmi; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2018)
This study aims to describe the learning motivation on Slow Learner students. Subjects of this study are two Slow Learner students in in Margosari elementary school.. This research uses descriptive qualitative research method and case study approach. Data collection is using participative observation techniques, in-depth interviews, documentation studies and questionnaires. The data validity test uses source and method triangulation. Data analysis uses Miles and Huberman data analysis that is data reduction, data presentation, and conclusion. The result of this research is that intrinsic and extrinsic learning motivation on Slow Learner students are high. The intrinsic motivation of Slow Learner students having a passion and desire to succeed, having a motivation about the need of study proven by the students that being active while learning, and having wishes and dreams of the future. While extrinsic motivation of students consists of the awards in learning, interesting learning activities and a conducive learning environment.